Medulance - Rochiramani, Harshit; Kulkarni, Vrushali; Sayeda, Raana (International Journal of Computer Sciences and Engineering, 2025)
Many application are providing location based services, like Ola and Uber in which they find the nearest ride and allocate that to user and travel to destination. But what in the case of an Ambulance that is in an emergency situation in such cases we need to find the best path possible so that the patient can be assisted immediately reducing the traveling time to minimum. What A* algorithm does is it connects two paths or nodes together it, while in an emergency situation we need the best path possible we are not challenging to improve the algorithm but we are integrating A* with some repositories just to be more efficient in finding path.